(untitled) (Encartes, 2022)
Post-ethnography pursues “micro-occurrences” and visual findings that have taken place in Tijuana in the past 28 years. These photographs show an iconography of white crosses, skulls, empty water jugs and cempasúchil flowers. Postphotography helps redimension this ethnographic evidence. Thus, the photo-essay speaks of sociocultural and artistic guerrillas against the strategic oblivion promoted by the governments of the U.S. and Mexico towards the deaths of migrants and the border walls as necro-artefacts in which art, solidarity and memory meet.